Does Health Education Through Videos and E-Leaflet Have a Good Influence on Improving Students’ Reproductive Health Knowledge, Attitudes, and Practices? an Intervention Study in Jatinangor, Indonesia - Yuliasih ND; Sari P; Bestari AD; Martini N; Sujatmiko B (Advances in Medical Education and Practice)
Neneng Dewi Yuliasih,1 Puspa Sari,1,2 Astuti Dyah Bestari,1,2 Neneng Martini,1,2 Budi Sujatmiko2 1Midwifery Program, Faculty of Medicine, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Department of Public Health, Faculty of Medicine, Universitas Padjadjaran, Sumedang, West Java, IndonesiaCorrespondence: Puspa Sari, Midwifery Program, Department of Public Health, Faculty of Medicine, Universitas Padjadjaran, Eyckman 38, Bandung, West Java, 40161, Indonesia, Tel +62 022 2032170, Email puspa.sari@unpad.ac.idBackground: Reproductive health issues remain a serious concern, especially for university students. The problem occurs due to a lack of knowledge about three primary threats to adolescent reproductive health, namely, sexuality, HIV / AIDS, and drug abuse, which will affect the attitudes and practices that university students will adopt related to reproductive health. This study aims to analyze the effect of reproductive health education through videos and e-leaflets on improving students’ reproductive health knowledge, attitudes, and practices. The hypothesis for this study was to explore the differences in knowledge, attitudes, and practices before and after the intervention.Methods: This study used a quasi-experimental design. Purposive sampling was used to select participants from four universities in the Jatinangor District. 166 female first-year university students were divided into the study group through video (n = 83) and the control group through e-leaflet (n = 83). A structured questionnaire assessed reproductive health knowledge, attitude, and behavior before and after the intervention. SPSS version 27.0 was used to analyze the data.Results: This study showed that university students’ knowledge, attitudes, and practice increased significantly after the intervention (p< 0.001). The comparison results between the intervention group and the control group did not show a significant difference in knowledge improvement (p> 0.001); however, they showed differences in attitude and behavior improvement (p< 0.001).Conclusion: Reproductive health education through video and e-leaflets is equally effective in improving first-year students’ knowledge, attitude, and practice. University support is necessary for reproductive health education among students.Keywords: health education, knowledge, attitude, practice, reproductive health